Al-Syaibānī Conception of Work in Kitāb al-Kasb and the Relevance to Gig Economy - Naufatti Aufa; Wahyu Akbar; Hanief Monady; Muhammad Riza Hafizi; Muhaimin (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
Gig economy, often promoted as a flexible labor solution, has led to structural issues including worker vulnerability, unequal relationships, and a diminished sense of work. This research analyzes the relevance of al-Imām al-Syaibānī concept of work through the Al-Kasb framework as a normative critique of gig economy practices and an ethical foundation for the digital economy. A normative-historical literature review method addresses the gap between gig economy's conceptual suitability with Islamic values and persistent empirical problems. Analysis includes critical reading of the Book of Al-Kasb, review of contemporary gig economy literature, and thematic analysis mapping conceptual correspondences. Results reveal three main points of convergence: the link between self-resilience and farḍu ‘ayn, consistency of workforce diversity with farḍu kifāyah, and conceptual alignment between platform symbiosis and mu'āwanah principle. However, the core issue lies in the failure to internalize Al-Kasb's spiritual-ethical dimensions within platform work practices. Theoretical contributions expand Al-Kasb as a framework for evaluating digital work. Practically, findings suggest strengthening gig workers' spirituality, enhancing platform social responsibility, and formulating justice-oriented protection policies. This research is limited by the absence of empirical testing on Muslim gig workers' subjective experiences.